Synopsis of lobatifrons species-group (Hymenoptera: Bethylidae, Rhabdepyris) from Neotropical region, with redefinition of the group - Stein, P. R.w.; Azevedo, C. O. (Zootaxa, 2007)
The lobatifrons species-group of Neotropical region is redefined as to include the Rhabdepyris species with appendicular process at cuspis in the male genitalia. Rhabdepyris latissimus sp. nov., R. callosus sp. nov., R. concavus sp. nov. and R. demissus sp. nov. are described and illustrated. New geographical records and taxonomical data on R. septemlineatus Kieffer, 1906, R. quinquilineatus Kieffer, 1906, R. luteipennis, Evans, 1965, R. atlanticus Rosmann & Azevedo, 2005 are provided. R. lobatifrons Kieffer, 1910 is a junior synonym of R. septemlineatus. A key to males are given.